CLIPPERS and its mimics: evaluation of new criteria for the diagnosis of CLIPPERS. Issue 9 (9th May 2019) - Taieb, Guillaume; Mulero, Patricia; Psimaras, Dimitri; van Oosten, Bob W; Seebach, Jörg D.; Marignier, Romain; Pico, Fernando; Rigau, Valérie; Ueno, Yuji; Duflos, Claire; Fominykh, Vera; Guiraud, Vincent; et al.
Abstract : Objective: To evaluate the accuracy of the recently proposed diagnostic criteria for chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS). Methods: We enrolled 42 patients with hindbrain punctate and/or linear enhancements (<3 mm in diameter) and tested the CLIPPERS criteria. Results: After a median follow-up of 50 months (IQR 25–82), 13 out of 42 patients were CLIPPERS-mimics: systemic and central nervous system lymphomas (n=7), primary central nervous system angiitis (n=4) and autoimmune gliopathies (n=2). The sensitivity and specificity of the CLIPPERS criteria were 93% and 69%, respectively. Nodular enhancement ( ≥ 3 mm in diameter), considered as a red flag in CLIPPERS criteria, was present in 4 out of 13 CLIPPERS-mimics but also in 2 out of 29 patients with CLIPPERS, explaining the lack of sensitivity. Four out of 13 CLIPPERS-mimics who initially met the CLIPPERS criteria displayed red flags at the second attack with a median time of 5.5 months (min 3, max 18), explaining the lack of specificity. One of these four patients had antimyelin oligodendrocyte glycoprotein antibodies, and the three remaining patients relapsed despite a daily dose of prednisone/prednisolone ≥ 30 mg and a biopsy targeting atypical enhancing lesions revealed a lymphoma. Conclusions: Our study highlights that (1) nodular enhancement should be considered more as an unusual finding than a red flag excluding the diagnosis of CLIPPERS; (2) red flags may occur up to 18 months after disease onset; (3) as opposed to CLIPPERS-mimics, no relapse occurs when the daily dose of prednisone/prednisolone is ≥ 30 mg; and (4) brain biopsy should target an atypical enhancing lesion when non-invasive investigations remain inconclusive.